Penentuan Ukuran Butir (Particle Size) Cu dan Ni pada Lapisan Cu/Ni Menggunakan Metode Scherrer Termodifikasi - Rizka Nuzul Islamiyati; Moh. Toifur (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
The Cu/Ni layer is a layer that can be used as a material for low temperature sensors. The coating can be made by means of electroplating. Electroplating has limitations in controlling the number and size of metal particles. Therefore, the purpose of this study was to determine the grain size of Cu and Ni in electroplated Cu/Ni layers at varying voltages from 6 to 8 volts using the modified Scherrer method and to analyze the effect of stress on grain size. The method used in this research is descriptive method using a quantitative approach. The results showed that the grain size of the Cu substrate was D= (0.5071 ± 0.06) nm. As for the Ni layer, stress affects grain size. A voltage of 7 volts can produce the largest grain size of 0.776059 nm.